Design of Bamboo Reinforced Concrete Beams Considering Variability in Tensile Strength of Bamboo - ICASP14; Bhardwaj, Bibek; Stoner, Michael; Pang, Weichiang (My University, 2023)
In recent years, the price of steel has soared, making steel reinforcement in concrete structures unaffordable for households in low-income countries. Seismic activities in low-income households, particularly those in developing countries, pose a significant threat to life and property to unreinforced concrete structures. The application of bamboo as an alternative to steel in reinforced concrete is still in its early stages of development. Unlike steel, bamboo is a natural material, and its structural properties vary greatly based on species, location, age, and geometric properties. Thus, the design of bamboo-reinforced concrete involves more uncertainties than steel-reinforced concrete. This research investigates the structural properties of bamboo and bamboo-reinforced concrete beams through experimental testing and Monte Carlo simulation. Tension tests were conducted on ﾑMoso' (Phyllostachys edulis) bamboo harvested in Clemson, United States, and the variabilities in the tensile strength and stiffness properties of the Moso bamboo were quantified. A set of tension tests was conducted in conjunction with moisture content tests each week to determine the optimum time for construction application after harvest, given the changes in strength and stiffness over time. It also served to capture the inherent variability of the bamboo material. To test the behavior of concrete reinforced with bamboo, four 25.4 cm x 35.6 cm x 3.66 m (10 in. x 14 in. x 12 ft.) concrete beams with bamboo reinforcement were tested under four-point bending. The interaction between bamboo and concrete was observed during the flexural tests. The findings derived from the tension testing of bamboo samples were utilized in a Monte Carlo simulation to generate an anticipated range of capacities for bamboo reinforced concrete beams. Subsequently, a comparative analysis was performed between the projected beam test outcomes and the actual results obtained. Based on preliminary analysis, applying the current method to estimate the capacity of steel-reinforced concrete beams to bamboo-reinforced concrete may result in an overestimation of the capacity. This could be attributed to the lack of proper quantification of the slip between the bamboo reinforcements and the concrete in the current model.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED